2014
DOI: 10.1093/nar/gku394
|View full text |Cite
|
Sign up to set email alerts
|

POSA: a user-driven, interactive multiple protein structure alignment server

Abstract: POSA (Partial Order Structure Alignment), available at http://posa.godziklab.org, is a server for multiple protein structure alignment introduced in 2005 (Ye,Y. and Godzik,A. (2005) Multiple flexible structure alignment using partial order graphs. Bioinformatics, 21, 2362–2369). It is free and open to all users, and there is no login requirement, albeit there is an option to register and store results in individual, password-protected directories. In the updated POSA server described here, we introduce two sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…In the initial view, PDBFlex provides a visualization of all set of coordinates in the same relative position, as identified by structural superposition. The rotations of structures in individual windows can also be synchronized, similarly to an option implemented in on our POSA server ( 16 ). The user has the option to turn on synchronized rotation of all structure views to investigate large differences between compared structures in a cluster.…”
Section: Using Pdbflexmentioning
confidence: 99%
“…In the initial view, PDBFlex provides a visualization of all set of coordinates in the same relative position, as identified by structural superposition. The rotations of structures in individual windows can also be synchronized, similarly to an option implemented in on our POSA server ( 16 ). The user has the option to turn on synchronized rotation of all structure views to investigate large differences between compared structures in a cluster.…”
Section: Using Pdbflexmentioning
confidence: 99%
“…APBS (Baker et al, 2001) and PDB2PQR (Dolinsky et al, 2007) in PyMOL were used to calculate the surface electrostatic potential map. Cealign in PyMOL and the POSA server (Li et al, 2014) were used for structure alignment and to calculate the root-mean-square deviation (r.m.s.d.). jF obs j À jF calc j = P hkl jF obs j.…”
Section: Sequence and Structure Analysismentioning
confidence: 99%
“…These structural variations have previously been suggested to account for the great variability in substrate specificity across the members of this superfamily (Lima et al, 1997), but conclusive evidence for this hypothesis has not yet been obtained. These differences are also reflected in the structure-based phylogenetic tree constructed using the POSA server (Li et al, 2014), which showed a common origin for all of the HINT homologues (chosen for the present study), which thus formed a single clade (Fig. 6).…”
Section: Figurementioning
confidence: 76%